1299 Reduction of red cell transfusions and donor exposure in preterm neonates by implementing a Patient Blood Management (PBM) system in a tertiary NICU. (17th August 2022) - Zorro, Carolina; Carpenter, Emily; Hickey, Ann; Harris, Christopher; Blankenstein, Emily Van
Abstract : Aims: To evaluate the impact of a Patient Blood Management(PBM) system on red cell transfusion (RCT) rate and donor exposure in preterm infants during the first month of life Methods: Design: Following a transfusion audit in 2016, a patient blood management (PBM) system was implemented including weekly ward round, near patient testing, individualization of sampling, gestational age based single donor allocation and teaching sessions. Re-audit was conducted in 2019. Inclusion criteria: All preterm infants <32 weeks gestation admitted to NICU in their first week, who remained as inpatients for >two weeks were included. Data collection: Data were collected retrospectively using electronic patient records and analysed in subgroups according to gestational age (<28 weeks and 28 to 31+6 weeks). Results: In 2016, 21 babies were born 22+6 – 31+3 weeks gestational age and received 137 RCTs; transfusion from single donor were 89.7%. In 2019, 31 babies were born 24+0 – 31+4 weeks gestational age and received 92 RCTs. For infants born <28 weeks, the RCT rate was significantly higher in 2016 compared to 2019 (9.82 vs 5.9, p<0.001). For infants born 28 to 31+6 weeks, the RCT rate was also significantly higher in 2016 (2.9 vs 1.57, p<0.001). Single donor exposure was reduced in 2019 compared to 2016 (92 RCTs from 57 donors compared to 137 RCTs from 123 donors, p<0.001) Conclusion: The introduction of PBM achieved a 40% reduction in RCTs for infants <28weeks and 46% in those 28-<32 weeks gestation with a 33% reduction in donor exposure. We advocate this model to minimise transfusion risk.